Force and deformation behaviour of roof truss system with cold-formed steel channel section - Tam, Ping Hau (2015)
Cold-formed steel is widely used in Malaysia’s construction for roof truss structures. This study aims to investigate the force and deformation behaviour of a roof truss system and evaluate the results from analytical and experimental investigation. One roof truss was constructed by using LC7510 cold-formed steel channel which is 5.4m long and 0.651m height with angle about 20 degree and eight concentrated loads were acting on the top chord. The deflection of the roof truss was analyzed by LVDT’s. STAAD Pro was used to carry out the analytical investigation. Three models with three load cases been modeled and compared with actual roof truss. The critical load case is Load Case 2 which leaded to higher deflections. The percentage difference on deflection between Model 1 with Load Case 2 is 15.4% and the roof truss failed on connection direct to the support due to buckling.